Pulmonary embolism diagnosis part 1: clinical assessment at the front door. Issue 12 (22nd July 2022) - Cafferkey, John; Serebriakoff, Philippa; de Wit, Kerstin; Horner, Daniel E; Reed, Matthew James
Abstract : This first of two practice reviews addresses pulmonary embolism (PE) diagnosis considering important aspects of PE clinical presentation and comparing evidence-based PE testing strategies. A companion paper addresses the management of PE. Symptoms and signs of PE are varied, and emergency physicians frequently use testing to 'rule out' the diagnosis in people with respiratory or cardiovascular symptoms. The emergency clinician must balance the benefit of reassuring negative PE testing with the risks of iatrogenic harms from over investigation and overdiagnosis.